Perbandingan Metode Geostatistik dari Hasil Estimasi Sumberdaya Nikel Laterit - jenius, (ReTII, 2021)
Nickel laterite is formed as a result of a long weathering process, through chemical weathering and supergene enrichment, mainly from ultramafic rocks under conditions of moderately hot temperatures and moderately high rainfall and controlled by fluctuating movements of the groundwater table. Laterite nickel ore constitutes 73% of the world's nickel resources and will be the dominant nickel source in the future. This study aims to analyze the comparison of geostatistical methods in the research area. This study was divided into several stages, namely: field data collection (drill data), data from this stage was used to determine the depth and distribution of the laterite zone. Laterite nickel content estimation was carried out in the limonite and saprolite zones. So that it can be known an accurate method in the research area. In this case, the methods compared are the Ordinary Kriging (OK) and Inverse Distance Weighting (IDW) methods to find out which method is the most accurate to be used in this study.